Numerical investigations on different configurations of a four-channel meso-scale planar combustor fueled by hydrogen/air mixture - Zuo, Wei (2020)
Multiple single-channel meso-scale combustors assembling into a multi-channel meso-scale planar combustor is a good solution for elevating the output power of the micro-thermophotovoltaic system. Consequently, how to assembly a multi-channel meso-scale planar combustor for achieving higher output power comes to be an interesting issue. In this work, four representative four-channel meso-scale planar combustors, namely, combustor A, combustor B, combustor C and combustor D are designed. Extensive numerical investigations are conducted to compare the wall temperature of the four combustors under various hydrogen mass flow rates, hydrogen/air equivalence ratios and solid materials. Two variables, namely, mean wall temperature and nonuniformity coefficient of wall temperature are defined for comparing the wall temperature of the four meso-scale combustors. It is found that the purely counterflow four-channel meso-scale planar combustor D has more uniform and higher wall temperature compared with other combustors. Furthermore, the detailed heat transfer mechanisms of four different four-channel meso-scale planar combustors are analyzed and presented. In addition, some critical values are proposed for keeping high and uniform wall temperature on the purely counterflow four-channel meso-scale planar combustor. This work offers us great reference value for the design of multi-channel meso-scale planar combustor.